Case reportTranscatheter closure of Blalock-Taussig anastomosis with brachial access in a child with obstruction of the left subclavian artery and secondary subclavian steal syndrome - Surmacz, Rafał; Moszura, Tomasz; Mroziński, Bartłomiej; Baszko, Artur; Wojtalik, Michał; Bobkowski, Waldemar; Siwińska, Aldona (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
In case of significant hypoxia in the course of congenital heart defect, when definite surgery is difficult, various palliative procedures are performed. One of the most frequently used is a modified Blalock-Taussig (BT) anastomosis. The BT anastomosis is closed during cardiac surgery. In some patients, BT anastomosis remains open after the surgery and requires closure by cardiac intervention using different types of closure devices. We describe a case of percutaneous closure of Blalock-Taussig anastomosis in a 4-year-old boy, with occluded left subclavian artery, presence of collateral circulation, and the subclavian artery steal syndrome to the left pulmonary artery through the patent BT anastomosis.